2020
DOI: 10.33255/3160/777
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de polimorfismos en los genes SOX6 y Ryr1 y su relación con la calidad de carne de cerdo

Abstract: Se estudió la incidencia de polimorfismos de los genes Ryr1 y SOX6 en una población porcina del noreste entrerriano. Ambos genes están relacionados con la calidad de carne, Ryr1 es responsable del síndrome de estrés porcino y carnes PSE, mientras que SOX6 es un factor de transcripción importante en la diferenciación de fibras musculares. Se analizó el efecto de dos SNPs de SOX6 y uno de Ryr1 con respecto a los atributos de calidad. Los resultados mostraron que el pH y la CRA se vieron influenciados significati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…If the carrier sows for the mutant allele are more prone to stress, it may be a prerequisite for reducing their reproductive ability. Regarding the susceptibility of certain breeds of pigs, Pietren, Polish-Chinese pigs, Landrace, Hampshire and Yorkshire are considered to be quite prone to stress while Chester White, Duroc, Large White and Berkshire are considered stress-resistant (Ivanov & Guk, 2019;Sipahelut et al, 2019;Rodríguez et al, 2020). In our studies, only 6.4% of animals carrying the mutant allele of the RYR1 gene were detected, while homozygous animals with the mutant allele of this gene were not detected at all.…”
Section: Discussionmentioning
confidence: 40%
“…If the carrier sows for the mutant allele are more prone to stress, it may be a prerequisite for reducing their reproductive ability. Regarding the susceptibility of certain breeds of pigs, Pietren, Polish-Chinese pigs, Landrace, Hampshire and Yorkshire are considered to be quite prone to stress while Chester White, Duroc, Large White and Berkshire are considered stress-resistant (Ivanov & Guk, 2019;Sipahelut et al, 2019;Rodríguez et al, 2020). In our studies, only 6.4% of animals carrying the mutant allele of the RYR1 gene were detected, while homozygous animals with the mutant allele of this gene were not detected at all.…”
Section: Discussionmentioning
confidence: 40%
“…Concerning the two CAST polymorphisms, CAST 638 Ser>Arg-and CAST 76,872 G > A , heterozygote's genotypes were the most numerous in both populations. And for SOX6 gene, allele A of SOX6 A SNP, described as favorable for fresh meat, was the most frequent in both populations and allele C of the SOX6 B SNP, associated with meat color and pH, was observed mainly in heterozygosis ( Zhang et al., 2015 ; Rodriguez et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that SOX6 A may influence pH and CRA, whereas allele C of SOX6 B may be linked just to pH in Halothane free animals. So, the selection of A allele for SOX6 A and C for SOX6 B could improve the production of good quality fresh meat (Rodriguez et al., 2020 ). These are the first results on SOX6 allele segregation reported in Argentine pig populations.…”
Section: Discussionmentioning
confidence: 99%